Burkina Faso : Poverty Reduction Strategy Paper Annual Progress Report. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2007)
This report reviews the Priority Action Program (PAP) for Poverty Reduction Strategy Paper (PRSP) implementation in Burkina Faso. The PAP makes the PRSP operational and increases the visibility of public policies in the area of poverty reduction. The 2005-07 PAP is expected to help remove obstacles to economic and social progress. By 2007, the aim is to reduce the overall poverty rate to 43.3 percent, with rural and urban poverty rates amounting to 48.1 percent and 16.6 percent, respectively.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet